Thyroid Function, Urinary Iodine, and Thyroid Antibody Status Among the Tribal Population of Kashmir Valley: Data From Endemic Zone of a Sub-Himalayan Region - Ganie, Mohd Ashraf; Charoo, Bashir A.; Sahar, Tajali; Bhat, Moomin Hussain; Ali, Sheikh Abid; Niyaz, Madiha; Sidana, Shivani; Yaseen, Arajmand (Frontiers in Public Health, 2020)
Background: There are scarce data on the prevalence of thyroid disorders and urinary iodine status among tribal populations of India, with no reported data from Kashmir valley. Objectives: To estimate the prevalence of thyroid disorders and evaluate urinary iodine concentration (UIC) and thyroid autoantibody status among Gujjar and Bakerwal tribes of Kashmir valley. Methods: This cross-sectional study recruited tribal subjects using multistage cluster sampling from 5 out of 22 districts of Jammu and Kashmir (J&K). Using a predesigned questionnaire, the details of past or current medical history and drug intake, including thyroid hormone medication etc. were recorded after obtaining an informed consent. Examination included anthropometry (height, weight, waist circumference), blood pressure measurement, and relevant general physical examination focusing on goiter palpation, while as laboratory assessment included estimation of serum thyroid hormone levels, antithyroid peroxidase antibody (anti-TPO Ab), and urinary iodine concentration. Results: A total of 763 subjects (56.4% women and 43.6% men) with a mean(±SD) age of 39.46 (±17.51) ranging from 10 to 85 years and mean(±SD) body mass index (BMI) of 21.28 (±4.16) kg/m2 were studied. Goiter was detected in 6.8%, while 33.2% subjects had some form of thyroid dysfunction (including 24.1% subclinical and 6.8% overt hypothyroidism). Subclinical and overt hyperthyroidism were observed in 1.3 and 0.9% of cases, respectively. Anti-TPO Ab was elevated in 13.6%, while the median [interquartile range (IQR)] for UIC was 154.50 (135) μg/L [156.13 (134) μg/L in men and 147.26 (136) μg/L in women]. A negative correlation was observed between UIC and anti-TPO Ab (r = −0.087, P = <0.05). Conclusion: These novel data on iodine and thyroid status among a tribal population of India generally inhabiting in remote sub-Himalayan belts demonstrate high prevalence of subclinical hypothyroidism (SCH) with persistent iodine deficiency. These preliminary data may warrant large well-designed studies to carry out comprehensive assessment of the problem in this high-risk and marginalized population.